The Impact of Nutrition Education Intervention on Parental Knowledge to Prevent Child Stunting - Laksmi Puspa Sari, Gusti Ayu Putu; Ari Kusuma Yana, I Gusti Agung; Irawati Wibowo, Yosi (State University of Gorontalo, 2025)
Stunting remains a significant health problem among children worldwide. Stunting has an impact on children's physical and cognitive development; if it is not addressed in the earliest stage, it can lead to decreased national productivity and economic growth. Whilst parents play a crucial role in preventing stunting in children, ensuring they have adequate knowledge is essential. This study aimed to determine the effect of educational intervention on the level of knowledge among parents in preventing child stunting. This is a pre-experimental study using a pretest and posttest design. This study involved a sample of 93 respondent in an area in the Bali area. The educational intervention involving a single session of health education focused on increasing knowledge about childhood stunting. Pre-test dan post-test was conducted before and after the intervention, and the results were categorized into good, simply and less. Pre-test and post-test data was analysed using a paired t-test. The results showed a significant increase in the percentage of parents with good knowledge from 11.8% in the pre-test to 30.1% in the post-test (p-value 0.001). This finding showed the effectiveness of educational interventions to enhance parental knowledge, which might increase their participation in preventing the risk of child stunting.